IMPLEMENTATION OF THE DISCOVERY LEARNING MODEL BASED ON THINK PAIR SHARE TO IMPROVE STUDENTS' LEARNING OUTCOMES - Lalita Manohari; Rini Purwati (Indonesian Journal of Educational Development (IJED), 2023)
This study aimed to improve student learning achievement through the application of think pair share-based discovery learning models. This type of research was classroom action research with the Kemmis & McTaggart research design. The location of this research was SMAN 1 Kuta Utara in class XII MIPA 4 with a total of 38 students as research subjects. The data analysis technique was carried out in a quantitative descriptive manner. The results of the data analysis showed that the application of the think pair share-based discovery learning model could improve student learning achievement with completeness in cycle I of 68.4% and increased in cycle II with completeness of 84.2%. Based on the results of data analysis, it could be concluded that the application of the discovery learning model based on think pair share could improve student learning outcomes.